Surface effects and hygroscopic properties of new smoothing compositions - Ткачук, Ганна Сергіївна; Щербань, Володимир Юрійович (Eastern-European Journal of Enterprise Technologies, 2009)
The properties of smoothing compositions for cotton, which excipient-fixing film is aluminum compounds. When using these substances improves adhesion to fiber dressing and technological parameters of the process of weaving through hygroscopic and plasticity of schlicht films